Economics of Information Security and Privacy - Moore, Tyler; Pym, David; Ioannidis, Christos; SpringerLink (Online service) (Boston, MA : Springer US, 2010)
The Workshop on the Economics of Information Security (WEIS) is the leading forum for interdisciplinary research and scholarship on information security and privacy, combining ideas, techniques, and expertise from the fields of economics, social science, business, law, policy, and computer science. In 2009, WEIS was held in London, at UCL, a constituent college of the University of London. Economics of Information Security and Privacy includes chapters presented at WEIS 2009, having been carefully reviewed by a program committee composed of leading researchers. Topics covered include identity theft, modeling uncertainty's effects, future directions in the economics of information security, economics of privacy, options, misaligned incentives in systems, cyber-insurance, and modeling security dynamics. Economics of Information Security and Privacy is designed for managers, policy makers, and researchers working in the related fields of economics of information security. Advanced-level students focusing on computer science, business management and economics will find this book valuable as a reference.
and Overview -- The Price of Uncertainty in Security Games -- Nobody Sells Gold for the Price of Silver: Dishonesty, Uncertainty and the UndergroundEconomy -- Security Economics and Critical National Infrastructure -- Internet Multi-Homing Problems: Explanations from Economics -- Modeling the Security Ecosystem - The Dynamics of (In)Security -- Modeling the Economic Incentives of DDoS Attacks: Femtocell Case Study -- The Privacy Jungle:On the Market for Data Protection in Social Networks -- The Policy Maker's Anguish: Regulating Personal Data Behavior Between Paradoxes and Dilemmas -- Valuating Privacy with Option Pricing Theory -- Optimal Timing of Information Security Investment: A Real Options Approach -- Competitive Cyber-Insurance and Internet Security -- Potential Rating Indicators for Cyberinsurance: An Exploratory Qualitative Study -- The Risk of Risk Analysis And its Relation to the Economics of Insider Threats -- Competition, Speculative Risks, and IT Security Outsourcing.
Keywords: Computer science; Computer network architectures; Computer Communication Networks; Data protection; Data structures (Computer science).; Economics; Computer Science; Systems and Data Security; Economics/Management Science, general; Computer Communication Networks; Data Structures, Cryptology and Information Theory; Computer Systems Organization and Communication Networks